REFERENCIAÇÃO TEXTUAL: DA SUBJETIVIDADE À REPRESENTAÇÃO DA IDENTIDADE FEMININA NO TEXTO ESCRITO - Dutra, Jaqueline Aparecida dos Santos (2012)
This research aims to investigate textual referentiation elements and strategies concentrating on linguistic forms that show subjectivity as well as a representation of the women identity in written texts, focusing on the violence against women. We based this work in referencial chains, emphasizing strategies of the textual referential and the observation of the linguistic choices made by text producers. In order to analyse the data identified, it was considered the language and referral from the perspective of social cognitive interaction, in which both are understood as a discursive activity that happens throughout the relations between subjects, considering the social universe where they act. We verified that categorized and (re)categorized strategies allow us to see in the analyzed texts the subjectivity and women identity representation in violence situations. The referentiation indicated that elements of subjectivity could be highlighted or deleted depending on the linguistic choices operated by the text producer. These choices are taken according to particular intentions and factors of social and cultural choices. Regarding women representation, we found that it is determined by the difference or opposition to the man. Our results indicated the elements of referentiation portray women and violence forms committed, are done in order to draw social attention to a common and worrying practice, colaboranting to rethink some attitudes, beliefs and collective values.